Repetition as a means of verbal and psychological violence in interrogation scenes from contemporary drama - Onič, Tomaž (Ars et humanitas, 2020)
The psychological and verbal pressure that often saturates the atmosphere in the interrogation scenes of certain subgenres of post-WWII drama can be achieved through various stylistic means. Among these are repetition and recurrence, which conveniently suit the nature of vicious interrogations, where questions (often illogical) are posed repeatedly, partly to extort information from the victim but predominantly to break the victim's resistance. Used in the ut - terances of the speaker, these repetitive questions or parts thereof intensify the distressing mood and strengthen the superiority of the speaker who intimidates, humiliates or otherwise degrades the victim. In this study, the focus will be on those instances of repetition and recurrence that contribute strongly to creating such situations and relationships in contemporary drama. The traditional iteration patterns will be identified, analysed and categorized according to the po - tential intensity of the repression and the schematic type of recurrence. The examples are taken from plays by Arthur Miller, Harold Pinter and Drago Jančar.
Keywords: besedilno nasilje; modern drama; ponavljanje; ponovne pojavitve; psihološko nasilje; psychological violence; recurrence; repetition; sodobna drama; verbal violence